IS THERE A CAUSAL RELATIONSHIP BETWEEN FINANCIAL PERFORMANCE AND PREMIUM PRODUCTION? EVIDENCE FROM TURKISH INSURANCE INDUSTRY - Murat Belke; Mohsin Shabir; Özcan Işık (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims at determining the causal link between financial performance and premium production of non-life insurance companies. The relation between the financial performance and premium production is explored employing data from the 2011-2019 period for eight Turkish non-life insurance companies. In the first stage of the analysis, a hybrid model including LOPCOW, SWARA II, and MARCOS methods is proposed to determine companies’ financial performance values. In this stage, a novel integrated weighting method for calculating criterion weights is applied based on objective information and judgements of decision-makers. In the second stage, the association between financial performance and premium production is investigated by correlation analysis. In the last stage, the causality linkage between the two variables is estimated using a panel causality test developed by Dumitrescu and Hurlin (2012). According to the results obtained from the panel causality test, the bidirectional causality relation exists between financial performance and premium production. Besides, the individual panel causality results reveal that bidirectional causality is valid for only Allianz and Anadolu insurance companies, which had an average share of over 35% in total non-life premium production during the analysis period. The paper provides fresh evidence on the association between the financial performance and premium production, particularly from the Turkish context.